You Can’t Fix What Is Not Broken: Contextualizing the Imbalance of Perceptions About Heritage Language Bilingualism - Bayram, Fatih; Kubota, Maki; Luque, Alicia; Pascual y Cabo, Diego; Rothman, Jason (Frontiers in Education, 2021)
In this article, (HSs) we discuss the perceptions of researchers who work on heritage language bilingualism (HLB), educators who teach heritage speakers (HSs), and, crucially, HSs themselves regarding the nature of bilingualism in general as well as HLB specifically. Despite the fact that all groups are invested in HLB and that researchers and educators tend to have a similar basic understanding of HLB development and share common goals regarding heritage language (HL) teaching and learning, there are non-trivial differences and disconnects between them. In our view, beyond the various aspects of the societal milieu that significantly contribute to this state of affairs, we maintain that these differences also reflect unfortunate miscommunication regarding how the object and outcomes of HLB research is packaged, contextualized and communicated to HSs and teachers who have direct influence over their education. Considering this, the main goal and contribution of the present work is to provide a forum in which the many voices involved in HL research/teaching/learning are acknowledged and the knock-on effects of such acknowledgement are meaningfully considered.